Prognostic Factors for Adrenocortical Carcinoma Outcomes - Scollo, Claudia; Russo, Marco; Trovato, Maria Antonietta; Sambataro, Daniela; Giuffrida, Dario; Manusia, Mario; Sapuppo, Giulia; Malandrino, Pasqualino; Vigneri, Riccardo; Pellegriti, Gabriella (Frontiers in Endocrinology, 2016)
Purpose: Adrenocortical cancer (ACC) is an aggressive tumor characterised by a high recurrence rate and poor response to treatment. This study analyses a consecutive series of ACC patients to evaluate the prognostic value of various clinical and pathological characteristics. Methods: We retrospectively evaluated 32 ACC patients followed at our Medical Center from 1997 to 2015 and evaluated the prognostic value of age at diagnosis, gender, tumor functional status, stage and type of treatment with respect to overall survival (OS) and disease-free survival (DFS) as determined by Kaplan–Meier curves. Results: ACC was associated with hormonal overproduction in 50% of cases, and patients with isolated hyperandrogenism had a better prognosis. Recurrence was observed in 12/26 (46.2%) patients with no evidence of disease after surgery. Tumor size (HR 1.32, 95% CI 1.12–1.64; p=0.007), ki-67 (HR 1.06, 95% CI 1.02–1.11; p=0.009) and advanced stage at diagnosis (III–IV) (HR 6.51, 95% CI 1.65–24.68; p=0.006) were associated with recurrence in the 26 R0 patients in the univariate analysis. Advanced stage was an independent risk factor for recurrence in the multivariate analysis (HR 8.10, 95% CI 1.55–41.35; p=0.01). Five-year survival was 40.0%. Positive resection margins (HR 10.61, 95% CI 3.02–38.31; p=<0.001), ki-67 (HR 1.04, 95% CI 1.01–1.07; p=0.01) and advanced stage (HR 11.31, 95% CI 1.45–87.76; p=0.02) were associated with poor survival in all 32 patients, but only positive resection margins were an independent predictor of mortality in the multivariate analysis (HR 6.22, 95% CI 1.44–26.05; p=0.01). Conclusions: ACC has a poor prognosis with a high recurrence rate. Tumor stage at diagnosis and the completeness of surgical excision are the most relevant prognostic factors.